Oral microbiota dysbiosis accelerates the development and onset of mucositis and oral ulcers - Min, Ziyang; Yang, Lei; Hu, Yu; Huang, Ruijie (Frontiers in Microbiology, 2023)
With the rapid development of metagenomic high-throughput sequencing technology, more and more oral mucosal diseases have been proven to be associated with oral microbiota shifts or dysbiosis. The commensal oral microbiota can greatly influence the colonization and resistance of pathogenic microorganisms and induce primary immunity. Once dysbiosis occurs, it can lead to damage to oral mucosal epithelial defense, thus accelerating the pathological process. As common oral mucosal diseases, oral mucositis and ulcers seriously affect patients’ prognosis and quality of life. However, from the microbiota perspective, the etiologies, specific alterations of oral flora, pathogenically changes, and therapy for microbiota are still lacking in a comprehensive overview. This review makes a retrospective summary of the above problems, dialectically based on oral microecology, to provide a new perspective on oral mucosal lesions management and aims at improving patients’ quality of life.